Pengaruh peran serta lingkungan ekologi belajar dan tingkat perkembangan diri siswa terhadap motivasi belajar Siswa Sekolah Dasar di Kecamatan Nalumsari Kabupaten Jepara - Anni Masudah (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to analyze the influence of the role of the ecological learning environment and the level of students' self-development on the learning motivation of elementary school students in Nalumsari District, Jepara Regency. This study uses a correlational quantitative approach. The object of the research includes three public elementary schools consisting of SDN 2 Bendanpete, SDN 1 Ngetuk and SDN 1 Bategede. The research subjects included students and their guardians from the three state elementary schools which had a population of 632 students and the sampling method used was the Slovin technique (n=87). Data collection techniques used the method of observation, documentation and questionnaires. Data analysis technique with regression analysis with SPSS. The results showed that partially the ecological learning environment had a significant positive effect on students' learning motivation. Likewise, student self-development has a significant positive effect on student learning motivation partially. The results of multiple linear regression showed that the coefficient value for the student's learning ecological environment variable had a significant negative effect on the student's learning motivation variable, while the student's level of self-development variable had a significant positive effect on the learning motivation variable.Â